South-South migration and the labor market: evidence from South Africa - Biavaschi, Costanza; Facchini, Giovanni; Mayda, Anna Maria; Mendola, Mariapia (Oxford University Press, 2018)
Using census data for 1996, 2001 and 2007 we study the labor market effect of immigration to South Africa. We exploit the variation – both at the district and at the national level –in the share of foreign–born male workers across schooling and experience groups over time. In addition, we use an instrumental variable empirical strategy to estimate the causal effect of immigration on the local labor market. At the district level, we show that increased immigration has a negative and significant effect on natives’ employment rates but not on total income. At the national level, we find that increased immigration has a negative and significant effect on natives’ total income but not on employment rates. Our results are consistent with outflows of natives to other districts as a consequence of migration, as in Borjas (2006).